Rancang Bangun Kendali Sistem Inverter Sinusoidal Pulse Width Modulation (SPWM) Frekuensi 25 Hz Dan 50Hz Berbasis Sensor Kelembapan Tanah Mengunakan Arduino Uno R3 - Riski Kurniawan; Antonius Rajagukguk (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
This study aims to create a two-frequency inverter control system, which works based on changes in the value of the soil moisture sensor, as a motor control for automatic plant sprinklers. In this study, the inverter is designed using the Sinusoidal pulse width modulation (SPWM) method, by amplifying the SPWM signal using IC IR2110, so that it is able to run the switching process in the h-bridge inverter circuit, the inverter voltage is increased with a step-up transformer and filtered using a low pass filter. The inverter output frequency is determined based on the YL-69 sensor value, with a control system based on Arduino uno. Based on the results of testing the inverter prototype, in wet soil moisture conditions with a percentage of less than 25%, the inverter is in standby mode, at the moisture content of the moist soil with a percentage between 25-40%, the inverter produces a frequency of 24.61 Hz, while the moisture content is 24,61 Hz. dry soil with a percentage of more than 40%, the inverter produces a frequency of 48,83 Hz. Based on the results of the prototype testing, it can be applied to coaching a single-phase induction motor type water pump in automatic plant sprinklers. Keywords: SPWM, IC 2110, H-bridge inverter, sensor YL-69, low pass filter